2008
DOI: 10.1177/0363546508314415
|View full text |Cite
|
Sign up to set email alerts
|

Control of Laxity in Knees with Combined Posterior Cruciate Ligament and Posterolateral Corner Deficiency

Abstract: Posterior cruciate ligament (PCL) injuries are associated commonly with posterolateral corner (PLC) injuries. 13,19,39,45 Injuries to the PLC, when associated with PCL injuries, are reported to be missed frequently. 26,29,34,40 Biomechanical studies have demonstrated that cutting the posterolateral structures increases the in situ forces on the PCL 28,37 ; recurrent laxity after PCL reconstruction is most commonly Background: Although many posterior cruciate ligament (PCL) injuries are in combination with post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…Albright and Brown used the sling procedure reconstructing PLC [1], but this method did not reconstruct the LCL or PFL anatomically. In a recent study, Apsingi et al [2] used nine cadaver knees to show that in combined PCL plus PLC‐deficient knees, combined single‐bundle PCL plus modified Larson PLC reconstruction was sufficient to restore posterior drawer, external rotation and varus laxity to normal. Although the attachments are nonanatomic in the modified Larson technique, this procedure is effective to restore the varus and external rotation functions of the knee at time zero post‐reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Albright and Brown used the sling procedure reconstructing PLC [1], but this method did not reconstruct the LCL or PFL anatomically. In a recent study, Apsingi et al [2] used nine cadaver knees to show that in combined PCL plus PLC‐deficient knees, combined single‐bundle PCL plus modified Larson PLC reconstruction was sufficient to restore posterior drawer, external rotation and varus laxity to normal. Although the attachments are nonanatomic in the modified Larson technique, this procedure is effective to restore the varus and external rotation functions of the knee at time zero post‐reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Sekiya et al [30] found that a combined double‐bundle PCL plus PLC reconstruction was capable of restoring both posterior translation and external rotation laxity to normal values. Apsingi et al [5] reported the same result, and also found that a combined single‐bundle PCL plus PLC reconstruction could restore these laxities to normal.…”
Section: Introductionmentioning
confidence: 67%
“…2 10 11 18 19 20 21 22 23 24 25 Outros, no entanto, não conseguiram demonstrar a superioridade de uma técnica sobre a outra (um feixe versus dois feixes). 12 13 26 27 28 29 Este cenário nos fez pensar se a comparação deveria ser feita entre um e dois feixes ou se, por outro lado, há um problema com o volume do enxerto, que seria mais bem resolvido com um único feixe mais espesso (e não com vários feixes). Em seguida, identificamos dois pontos-chave para um estudo mais aprofundado: a espessura do enxerto e o segundo túnel femoral.…”
Section: Discussionunclassified